Thomas Van Nortwick. Somewhere I Have Never Travelled. The Hero's Journey. New York-Oxford, Oxford University Press, 1996, 204 pp. - Errecalde, Alejandro Martín (1997)
Fil: Errecalde, Alejandro Martín. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación; Argentina.